Coated lithium cobalt oxide positive electrode material and positive electrode plate prepared from same

By doping magnesium into the lithium cobalt oxide material and coating the conductive polymer and organic porous polymer, the modified conductive agent is thiolated and double-bonded ended disulfide bond-containing compounds, the problem of poor structural stability of lithium cobalt oxide material at high voltage is solved, and the high cycle stability and safety of the positive electrode sheet of the lithium battery is achieved.

CN119674042AActive Publication Date: 2025-03-21NANJING HANRUI NEW MATERIALS CO LTD

Patent Information

Application Number
CN202510000921.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-21
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The existing lithium cobalt oxide materials have poor structural stability at high voltages and cannot meet the market's demand for increased energy density of lithium-ion batteries.

Method used

By doping magnesium into lithium cobalt oxide material, its crystal structure is stabilized, and its surface is coated with conductive polymer polypyrrole and organic porous polymer, the modified conductive agent is thiolated and double-bonded grafting of disulfide-containing compounds, forming a binder with both hydrogen bonds and disulfide bonds.

Benefits of technology

It significantly improves the cycle stability of the positive electrode plate of lithium battery, enhances the durability and safety of the battery, and meets the market's demand for high energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery materials, in particular to a coated lithium cobalt oxide positive electrode material and a positive electrode plate prepared from the coated lithium cobalt oxide positive electrode material. A binder with dynamic reversible bonds such as a hydrogen bond and a disulfide bond is synthesized through free radical polymerization among acrylamide, acrylic acid and a double-bond-terminated disulfide bond-containing compound; the preparation method comprises the following steps: doping lithium cobalt oxide with Mg, coating the surface of the lithium cobalt oxide with a conductive polymer polypyrrole, and coating the surface of the lithium cobalt oxide with an organic porous polymer prepared from a quaternary connector 5, 10, 15, 20-tetra (4-aminophenyl) porphyrin and pyromellitic dianhydride by using a large pi bond of the polypyrrole; the conductive agent is modified, (3-mercaptopropyl) trimethoxysilane is firstly used for sulfhydrylation, then sulfydryl-double bond light click is utilized, and a double-bond end-capped disulfide bond-containing compound with a reversible bond is grafted, so that the stability and the safety of the battery performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a positive electrode material coated with lithium cobalt oxide and a positive electrode sheet prepared therefrom. Background Art

[0002] With the vigorous development of new energy, environmentally friendly, cycle-stable, and high-specific-capacity lithium-ion batteries have attracted much attention. As the main component of lithium-ion batteries, the performance of the positive electrode directly affects the capacity and cycle performance of lithium-ion batteries. The positive electrode is generally prepared by coating the positive electrode slurry on the surface of a metal foil layer, wherein the positive electrode slurry is generally composed of a positive electrode active material, a modified conductive agent, a binder, and a solvent. Lithium cobalt oxide is one of the mainstream positive electrode active materials in the current market. As the market's requirements for the energy density of lithium-ion batteries become higher and higher, the demand for increasing the upper limit voltage of lithium cobalt oxide charging has also become urgent.

[0003] Existing lithium cobalt oxide materials have poor structural stability under high voltage and cannot meet market demand. Summary of the invention

[0004] The object of the present invention is to provide a coated lithium cobalt oxide positive electrode material and a positive electrode plate prepared therefrom, so as to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing a coated lithium cobalt oxide positive electrode material comprises the following steps:

[0007] S1: adding the self-repairing adhesive into deionized water, stirring and then vacuuming to remove bubbles, to obtain a self-repairing adhesive solution, which is divided into two parts, denoted as self-repairing adhesive solution a and self-repairing adhesive solution b;

[0008] S2: Mix the self-healing glue a and the composite lithium cobalt oxide, and stir them ultrasonically. Then, add the modified conductive agent and the self-healing glue b in sequence, and stir them ultrasonically to obtain a coated lithium cobalt oxide positive electrode material.

[0009] Furthermore, the mass ratio of self-repairing glue a to self-repairing glue b is 3:1.

[0010] Furthermore, in terms of weight, the contents of the components in the positive electrode material are: 77-87 parts of composite lithium cobalt oxide, 6-9 parts of modified conductive agent, 4-8 parts of self-healing binder, and 21-26 parts of deionized water.

[0011] Furthermore, the preparation of composite lithium cobalt oxide includes the following steps:

[0012] (1) Cobalt trioxide powder, lithium carbonate powder and magnesium oxide are mixed, ground, and kept at 1000° C. for 10 hours in an air atmosphere to obtain magnesium-doped lithium cobalt oxide;

[0013] (2) Mix pyrrole, magnesium-doped lithium cobalt oxide, and anhydrous ethanol, add sodium persulfate, stir in an ice-water bath for 5-6 hours, filter, wash, and dry to obtain pyrrole-coated magnesium-doped lithium cobalt oxide;

[0014] (3) 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, pyromellitic anhydride, N-methylpyrrolidone and 1,3,5-trimethylbenzene are mixed, isoquinoline is added, ultrasonic mixing is performed for 10-20 min, the mixture is transferred to a reaction tube, freeze-degassing is repeated for 3-5 times, the mixture is kept at 150°C for 5 d, the mixture is cooled, centrifuged, washed with N,N-dimethylformamide and methanol for 3-5 times, tetrahydrofuran and pyrrole-coated magnesium-doped lithium cobalt oxide are added, the mixture is ultrasonically stirred for 1-2 h, centrifuged, washed and dried to obtain composite lithium cobalt oxide.

[0015] Furthermore, the preparation of the self-repairing adhesive comprises the following steps:

[0016] In a nitrogen atmosphere, acrylamide, acrylic acid, a double-bond-terminated disulfide-containing compound and deionized water are mixed, ammonium persulfate is added, the mixture is kept warm in an oil bath at 48-52° C. for 7-8 hours, washed with ethanol for 3-5 times, and freeze-dried to obtain a self-healing adhesive.

[0017] Further, the preparation of the modified conductive agent comprises the following steps:

[0018] 1) The conductive agent, isopropanol and deionized water are mixed, ultrasonically treated for 30-40 minutes, (3-mercaptopropyl)trimethoxysilane is added, the pH value is adjusted to 2.9-3.1, and the mixture is kept in a water bath at 58-62°C for 5-6 hours, filtered, washed and dried to obtain a mercapto conductive agent;

[0019] 2) Mix the thiol conductive agent and n-hexane, keep warm in a 60°C water bath for 3-4 hours, add a mixed solution of a double-bond-terminated disulfide-containing compound and n-hexane, stir for 5-6 hours, add benzoin dimethyl ether, treat with ultraviolet light, wash and dry to obtain a modified conductive agent.

[0020] Furthermore, the conductive agent is obtained by compounding carbon black and white carbon black in a mass ratio of 2:1.

[0021] Furthermore, the working conditions of the ultraviolet light treatment are: irradiation with a 365nm ultraviolet lamp for 1 hour.

[0022] Furthermore, the preparation of the double bond-terminated disulfide bond-containing compound comprises the following steps:

[0023] Under a nitrogen atmosphere, 4,4-diaminodiphenyl disulfide and acetone are mixed, 2-isocyanate ethyl methacrylate is added, and the mixture is stirred at 18-25° C. for 20-21 hours, washed, and dried to obtain a double-bond-terminated disulfide-containing compound.

[0024] Furthermore, a method for preparing a positive electrode sheet coated with lithium cobalt oxide comprises the following steps: coating the positive electrode material coated with lithium cobalt oxide on both sides of a metal foil, and drying the metal foil to obtain a positive electrode sheet coated with lithium cobalt oxide.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention provides a lithium cobalt oxide coated positive electrode material and a positive electrode plate prepared therefrom, which, through process and component limitation, endows the positive electrode plate of a lithium battery with excellent cycle stability, thereby improving the durability and safety of the lithium battery.

[0027] Traditional lithium battery positive and negative electrodes mostly use polyvinylidene fluoride as a binder, which is easy to shed powder and cannot withstand the huge deformation during the positive and negative electrode cycles after long-term use. In addition, in the preparation process, N-methylpyrrolidone, an organic solvent with high cost and harmful to the human body, is often used as a solvent. The present invention, based on the purpose of reducing costs and increasing efficiency, uses a more economical water-based binder as a positive electrode binder to meet green production requirements and is conducive to its market promotion. A binder with dynamic reversible bonds such as hydrogen bonds and disulfide bonds is synthesized by free radical polymerization between acrylamide, acrylic acid, and a double-bond-terminated disulfide bond-containing compound, wherein the double-bond-terminated disulfide bond-containing compound is prepared from 4,4-diaminodiphenyl disulfide and 2-isocyanate ethyl methacrylate, which effectively improves the mechanical properties and rheological properties of the positive electrode material and improves the stability of the electrode sheet. At the same time, the abundant polar groups on the binder can form a covalent-non-covalent cross-linked network between the conductive particles and the copolymer chain, effectively buffering the volume expansion of white carbon black, so that the structural integrity of the electrode can remain unchanged after the cycle.

[0028] In order to improve the stability of lithium cobalt oxide, Mg is firstly used for doping in the present invention to stabilize its crystal structure and inhibit its irreversible phase change under high voltage, and then the conductive polymer polypyrrole is coated on its surface. Then, the large π bond of polypyrrole is utilized to coat the surface of the organic porous polymer prepared by the quaternary linker 5,10,15,20-tetrakis(4-aminophenyl)porphyrin and pyromellitic anhydride, thereby improving its effect on cycle performance and rate performance.

[0029] The conductive agent is modified by first thiolation with (3-mercaptopropyl)trimethoxysilane, and then photo-clicking with the thiol-double bond is used to graft a double-bond-terminated disulfide-containing compound with a reversible bond, thereby improving the stability and safety of battery performance. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

[0032] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0033] Embodiment 1: A method for preparing a positive electrode sheet coated with lithium cobalt oxide, comprising the following steps:

[0034] The positive electrode material coated with lithium cobalt oxide is coated on both sides of the metal foil and dried to obtain a positive electrode sheet coated with lithium cobalt oxide;

[0035] A method for preparing a coated lithium cobalt oxide positive electrode material comprises the following steps:

[0036] S1: adding the self-repairing adhesive into deionized water, stirring and then vacuuming to remove bubbles, to obtain a self-repairing adhesive solution, which is divided into two parts, denoted as self-repairing adhesive solution a and self-repairing adhesive solution b;

[0037] The mass ratio of the self-repairing glue a to the self-repairing glue b is 3:1;

[0038] The preparation of the self-repairing adhesive comprises the following steps:

[0039] Under nitrogen atmosphere, 3.2 g acrylamide, 3.2 g acrylic acid, 1.4 g double bond-terminated disulfide-containing compound, and 115 mL deionized water were mixed, 39 mg ammonium persulfate was added, and the mixture was kept in an oil bath at 48 °C for 8 h, washed with ethanol three times, and freeze-dried to obtain a self-healing adhesive;

[0040] The preparation of the double bond-terminated disulfide bond-containing compound comprises the following steps:

[0041] Under nitrogen atmosphere, 2.5 g of 4,4-diaminodiphenyl disulfide and 50 mL of acetone were mixed, 2.9 mL of 2-isocyanate ethyl methacrylate was added, and the mixture was stirred at 18°C ​​for 21 h, washed and dried to obtain a double bond-terminated disulfide bond-containing compound;

[0042] S2: mixing the self-repairing glue a and the composite lithium cobalt oxide, stirring them ultrasonically, adding the modified conductive agent and the self-repairing glue b in sequence, stirring them ultrasonically, and obtaining a coated lithium cobalt oxide positive electrode material;

[0043] In terms of weight, the content of each component in the positive electrode material is: 77 parts of composite lithium cobalt oxide, 6 parts of modified conductive agent, 4 parts of self-repairing binder, and 21 parts of deionized water;

[0044] The preparation of the composite lithium cobalt oxide comprises the following steps:

[0045] (1) 2.5 g of cobalt tetroxide powder, 1.2 g of lithium carbonate powder, and 0.4 g of magnesium oxide were mixed, ground, and kept at 1000° C. for 10 h in an air atmosphere to obtain magnesium-doped lithium cobalt oxide;

[0046] (2) 0.1 g of pyrrole, 10 g of magnesium-doped lithium cobalt oxide, and 20 mL of anhydrous ethanol were mixed, 0.4 mg of sodium persulfate was added, and the mixture was stirred in an ice-water bath for 5 h. The mixture was filtered, washed, and dried to obtain pyrrole-coated magnesium-doped lithium cobalt oxide;

[0047] (3) 0.2 mmol 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, 0.4 mmol pyromellitic anhydride, 3 mL N-methylpyrrolidone, and 3 mL 1,3,5-trimethylbenzene were mixed, 0.5 mL isoquinoline was added, ultrasonic mixing was performed for 10 min, the mixture was transferred to a reaction tube, freeze-degassing cycle was repeated 3 times, the mixture was kept at 150 °C for 5 d, cooled, centrifuged, washed with N,N-dimethylformamide and methanol 3 times in sequence, 10 mL tetrahydrofuran and 100 mg pyrrole-coated magnesium-doped lithium cobalt oxide were added, ultrasonic stirring was performed for 1 h, centrifuged, washed, and dried to obtain composite lithium cobalt oxide;

[0048] The preparation of the modified conductive agent comprises the following steps:

[0049] 1) 25 g of conductive agent, 0.4 L of isopropanol and 100 mL of deionized water were mixed, ultrasonically treated for 30 min, 5 g of (3-mercaptopropyl)trimethoxysilane was added, the pH value was adjusted to 2.9, and the mixture was kept in a 58°C water bath for 6 h, filtered, washed and dried to obtain a mercapto conductive agent;

[0050] 2) 4.2 g of thiolated conductive agent and 20 mL of n-hexane were mixed, kept in a 60°C water bath for 3 h, 3.6 g of a double-bond-terminated disulfide-containing compound and 20 mL of n-hexane were added, stirred for 5 h, 15.6 mg of benzoin dimethyl ether was added, treated with ultraviolet light, washed and dried to obtain a modified conductive agent;

[0051] The conductive agent is obtained by compounding carbon black and white carbon black in a mass ratio of 2:1;

[0052] The working conditions of ultraviolet light treatment are: irradiation with 365nm ultraviolet lamp for 1h.

[0053] Embodiment 2: A method for preparing a positive electrode sheet coated with lithium cobalt oxide, comprising the following steps:

[0054] The positive electrode material coated with lithium cobalt oxide is coated on both sides of the metal foil and dried to obtain a positive electrode sheet coated with lithium cobalt oxide;

[0055] A method for preparing a coated lithium cobalt oxide positive electrode material comprises the following steps:

[0056] S1: adding the self-repairing adhesive into deionized water, stirring and then vacuuming to remove bubbles, to obtain a self-repairing adhesive solution, which is divided into two parts, denoted as self-repairing adhesive solution a and self-repairing adhesive solution b;

[0057] The mass ratio of the self-repairing glue a to the self-repairing glue b is 3:1;

[0058] The preparation of the self-repairing adhesive comprises the following steps:

[0059] Under nitrogen atmosphere, 3.2 g acrylamide, 3.2 g acrylic acid, 1.4 g double bond-terminated disulfide-containing compound, and 115 mL deionized water were mixed, 39 mg ammonium persulfate was added, and the mixture was kept in a 50 °C oil bath for 7.5 h, washed with ethanol 4 times, and freeze-dried to obtain a self-healing adhesive;

[0060] The preparation of the double bond-terminated disulfide bond-containing compound comprises the following steps:

[0061] Under nitrogen atmosphere, 2.5 g of 4,4-diaminodiphenyl disulfide and 50 mL of acetone were mixed, 2.9 mL of 2-isocyanate ethyl methacrylate was added, and the mixture was stirred at 20° C. for 20.5 h, washed, and dried to obtain a double bond-terminated disulfide bond-containing compound;

[0062] S2: mixing the self-repairing glue a and the composite lithium cobalt oxide, stirring them ultrasonically, adding the modified conductive agent and the self-repairing glue b in sequence, stirring them ultrasonically, and obtaining a coated lithium cobalt oxide positive electrode material;

[0063] In terms of weight, the content of each component in the positive electrode material is: 83 parts of composite lithium cobalt oxide, 7 parts of modified conductive agent, 6 parts of self-repairing binder, and 23 parts of deionized water;

[0064] The preparation of the composite lithium cobalt oxide comprises the following steps:

[0065] (1) 2.5 g of cobalt tetroxide powder, 1.2 g of lithium carbonate powder, and 0.4 g of magnesium oxide were mixed, ground, and kept at 1000° C. for 10 h in an air atmosphere to obtain magnesium-doped lithium cobalt oxide;

[0066] (2) 0.1 g pyrrole, 10 g magnesium-doped lithium cobalt oxide, and 20 mL anhydrous ethanol were mixed, 0.4 mg sodium persulfate was added, and the mixture was stirred in an ice-water bath for 5.5 h, filtered, washed, and dried to obtain pyrrole-coated magnesium-doped lithium cobalt oxide;

[0067] (3) 0.2 mmol 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, 0.4 mmol pyromellitic anhydride, 3 mL N-methylpyrrolidone, and 3 mL 1,3,5-trimethylbenzene were mixed, 0.5 mL isoquinoline was added, ultrasonic mixing was performed for 15 min, the mixture was transferred to a reaction tube, freeze-degassing cycle was repeated 4 times, the mixture was kept at 150 °C for 5 d, cooled, centrifuged, washed with N,N-dimethylformamide and methanol 4 times in sequence, 10 mL tetrahydrofuran and 100 mg pyrrole-coated magnesium-doped lithium cobalt oxide were added, ultrasonic stirring was performed for 1.5 h, centrifuged, washed, and dried to obtain composite lithium cobalt oxide;

[0068] The preparation of the modified conductive agent comprises the following steps:

[0069] 1) 25 g of conductive agent, 0.4 L of isopropanol and 100 mL of deionized water were mixed, ultrasonically treated for 35 min, 5 g of (3-mercaptopropyl)trimethoxysilane was added, the pH value was adjusted to 3, and the mixture was kept in a 60°C water bath for 5.5 h, filtered, washed and dried to obtain a mercapto conductive agent;

[0070] 2) 4.2 g of thiolated conductive agent and 20 mL of n-hexane were mixed, kept in a 60°C water bath for 3.5 h, 3.6 g of a double-bond-terminated disulfide-containing compound and 20 mL of n-hexane were added, stirred for 5.5 h, 15.6 mg of benzoin dimethyl ether was added, treated with ultraviolet light, washed and dried to obtain a modified conductive agent;

[0071] The conductive agent is obtained by compounding carbon black and white carbon black in a mass ratio of 2:1;

[0072] The working conditions of ultraviolet light treatment are: irradiation with 365nm ultraviolet lamp for 1h.

[0073] Embodiment 3: A method for preparing a positive electrode sheet coated with lithium cobalt oxide, comprising the following steps:

[0074] The positive electrode material coated with lithium cobalt oxide is coated on both sides of the metal foil and dried to obtain a positive electrode sheet coated with lithium cobalt oxide;

[0075] A method for preparing a coated lithium cobalt oxide positive electrode material comprises the following steps:

[0076] S1: adding the self-repairing adhesive into deionized water, stirring and then vacuuming to remove bubbles, to obtain a self-repairing adhesive solution, which is divided into two parts, denoted as self-repairing adhesive solution a and self-repairing adhesive solution b;

[0077] The mass ratio of the self-repairing glue a to the self-repairing glue b is 3:1;

[0078] The preparation of the self-repairing adhesive comprises the following steps:

[0079] Under nitrogen atmosphere, 3.2 g acrylamide, 3.2 g acrylic acid, 1.4 g double bond-terminated disulfide-containing compound, and 115 mL deionized water were mixed, 39 mg ammonium persulfate was added, and the mixture was kept in an oil bath at 52 °C for 7 h, washed with ethanol 5 times, and freeze-dried to obtain a self-healing adhesive;

[0080] The preparation of the double bond-terminated disulfide bond-containing compound comprises the following steps:

[0081] Under nitrogen atmosphere, 2.5 g of 4,4-diaminodiphenyl disulfide and 50 mL of acetone were mixed, 2.9 mL of 2-isocyanate ethyl methacrylate was added, and the mixture was stirred at 25°C for 20 h, washed and dried to obtain a double bond-terminated disulfide bond-containing compound;

[0082] S2: mixing the self-repairing glue a and the composite lithium cobalt oxide, stirring them ultrasonically, adding the modified conductive agent and the self-repairing glue b in sequence, stirring them ultrasonically, and obtaining a coated lithium cobalt oxide positive electrode material;

[0083] In terms of weight, the content of each component in the positive electrode material is: 87 parts of composite lithium cobalt oxide, 9 parts of modified conductive agent, 8 parts of self-repairing binder, and 26 parts of deionized water;

[0084] The preparation of the composite lithium cobalt oxide comprises the following steps:

[0085] (1) 2.5 g of cobalt tetroxide powder, 1.2 g of lithium carbonate powder, and 0.4 g of magnesium oxide were mixed, ground, and kept at 1000° C. for 10 h in an air atmosphere to obtain magnesium-doped lithium cobalt oxide;

[0086] (2) 0.1 g of pyrrole, 10 g of magnesium-doped lithium cobalt oxide, and 20 mL of anhydrous ethanol were mixed, 0.4 mg of sodium persulfate was added, and the mixture was stirred in an ice-water bath for 6 h. The mixture was filtered, washed, and dried to obtain pyrrole-coated magnesium-doped lithium cobalt oxide;

[0087] (3) 0.2 mmol 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, 0.4 mmol pyromellitic anhydride, 3 mL N-methylpyrrolidone, and 3 mL 1,3,5-trimethylbenzene were mixed, 0.5 mL isoquinoline was added, ultrasonic mixing was performed for 20 min, the mixture was transferred to a reaction tube, and the mixture was freeze-degassed for 5 times, kept at 150 °C for 5 d, cooled, centrifuged, and washed with N,N-dimethylformamide and methanol for 5 times in sequence, 10 mL tetrahydrofuran and 100 mg pyrrole-coated magnesium-doped lithium cobalt oxide were added, ultrasonic stirring was performed for 2 h, centrifuged, washed, and dried to obtain composite lithium cobalt oxide;

[0088] The preparation of the modified conductive agent comprises the following steps:

[0089] 1) 25 g of conductive agent, 0.4 L of isopropanol and 100 mL of deionized water were mixed, ultrasonically treated for 40 min, 5 g of (3-mercaptopropyl)trimethoxysilane was added, the pH value was adjusted to 3.1, and the mixture was kept in a water bath at 62 °C for 5 h, filtered, washed and dried to obtain a mercapto conductive agent;

[0090] 2) Mix 4.2 g of thiolated conductive agent and 20 mL of n-hexane, keep warm in a 60°C water bath for 4 h, add a mixture of 3.6 g of a double-bond-terminated disulfide-containing compound and 20 mL of n-hexane, stir for 6 h, add benzoin dimethyl ether, treat with ultraviolet light, wash and dry to obtain a modified conductive agent;

[0091] The conductive agent is obtained by compounding carbon black and white carbon black in a mass ratio of 2:1;

[0092] The working conditions of ultraviolet light treatment are: irradiation with 365nm ultraviolet lamp for 1h.

[0093] Comparative Example 1: Taking Example 3 as the control group, the self-healing adhesive was replaced with polyacrylic acid (P104272: Aladdin reagent), and the other processes were normal.

[0094] Comparative Example 2: Taking Example 3 as the control group, magnesium-doped lithium cobalt oxide was used to replace the composite lithium cobalt oxide, and other processes were normal.

[0095] Comparative Example 3: Taking Example 3 as the control group, the modified conductive agent was replaced by carbon black, and the other processes were normal.

[0096] The thickness of the positive electrode material after solidification on the surface of the metal foil (aluminum foil) is 100µm.

[0097] Sources of raw materials used (for demonstration purposes only):

[0098] 5,10,15,20-Tetrakis(4-aminophenyl)porphyrin S44659: Shanghai Yuanye Biotechnology Co., Ltd.; acrylamide A108465, acrylic acid A103526, 4,4-diaminodiphenyl disulfide A101817, 2-isocyanate ethyl methacrylate I121957, cobalt tetraoxide powder C111617, lithium carbonate powder L101679, magnesium oxide M103940, pyrrole P104878, pyromellitic anhydride P109616, N-methyl Pyrrolidone M103246, 1,3,5-trimethylbenzene T105015, isoquinoline I105573, N,N-dimethylformamide D111999, tetrahydrofuran T103263, (3-mercaptopropyl)trimethoxysilane M100619, benzoin dimethyl ether B104003, carbon black C742510, white carbon S104599: Aladdin reagent; ammonium persulfate, ethanol, acetone, sodium persulfate, methanol, isopropanol, n-hexane, analytical grade: Sinopharm reagent.

[0099] Performance test: The positive electrode sheets prepared in the embodiments and comparative examples were tested:

[0100] The metal lithium sheet was used as the counter electrode, the prepared electrode sheet was used as the working electrode, and the battery was assembled for testing. The diaphragm used was polypropylene Celgard2400 (industrial grade), and the electrolyte was a LiPF6 carbonate solution with a concentration of 1 mol / L (the solvent was a carbonate with a volume ratio of EC, DEC, and DMC of 1:1:1);

[0101] Cycling performance: At 45°C, charge to 4.5V at 1.5C constant current and constant voltage for 5 minutes, then discharge to 3V at 0.7C constant current for 5 minutes, cycle charge and discharge 500 times, and test capacity retention rate;

[0102] Heating test: The charged battery is heated to 90°C for 2 hours to observe whether the battery discharges. If it does not discharge, the temperature is raised to 149°C for 2 hours. Ten batteries prepared in the embodiment and the comparative example are taken respectively. If none of them catch fire or explode, they are qualified.

[0103] Overcharge test: Charge at 4.6V for 7h, take 10 batteries prepared in the embodiment and the comparative example, and all the batteries that do not catch fire or explode are qualified. The results are shown in Table 1.

[0104] Table 1

[0105]

[0106] The present invention provides a positive electrode material coated with lithium cobalt oxide and a positive electrode plate prepared therefrom, which, through process and component limitation, endows the positive electrode plate of a lithium battery with excellent cycle stability, thereby improving the durability and safety of the battery.

[0107] By comparing Example 3 with Comparative Example 1, it can be seen that a binder having dynamic reversible bonds such as hydrogen bonds and disulfide bonds is synthesized by free radical polymerization between acrylamide, acrylic acid, and a double-bond-terminated disulfide bond-containing compound, wherein the double-bond-terminated disulfide bond-containing compound is prepared from 4,4-diaminodiphenyl disulfide and 2-isocyanate ethyl methacrylate, which effectively improves the mechanical properties and rheological properties of the positive electrode material and the stability of the electrode sheet. At the same time, the abundant polar groups on the binder can form a covalent-non-covalent cross-linked network between the conductive particles and the copolymer chains, effectively buffering the volume expansion of white carbon black, so that the structural integrity of the electrode can remain unchanged after cycling.

[0108] By comparing Example 3 with Comparative Example 2, it can be seen that in order to improve the stability of lithium cobalt oxide, Mg is first used for doping in the present invention to stabilize its crystal structure and inhibit its irreversible phase change under high voltage, and then the conductive polymer polypyrrole is coated on its surface, and then the large π bond of polypyrrole is used to coat the surface of an organic porous polymer prepared by a quaternary linker 5,10,15,20-tetrakis(4-aminophenyl)porphyrin and pyromellitic anhydride, thereby improving its effect on cycle performance and rate performance.

[0109] By comparing Example 3 with Comparative Example 3, it can be seen that by modifying the conductive agent, first thiolating it with (3-mercaptopropyl)trimethoxysilane, and then utilizing thiol-double bond photoclicking to graft a double-bond-terminated disulfide bond-containing compound with a reversible bond, the stability and safety of the battery performance are improved.

[0110] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a coated lithium cobalt oxide positive electrode material, characterized in that: The following steps are involved: S1: adding the self-repairing adhesive into deionized water, stirring and then vacuuming to remove bubbles, to obtain a self-repairing adhesive solution, which is divided into two parts, denoted as self-repairing adhesive solution a and self-repairing adhesive solution b; S2: Mix the self-healing glue a and the composite lithium cobalt oxide, and ultrasonically stir them. Then, add the modified conductive agent and the self-healing glue b in sequence, and ultrasonically stir them to obtain a coated lithium cobalt oxide positive electrode material.

2. The method for preparing a coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The mass ratio of the self-repairing glue a to the self-repairing glue b is 3:

1.

3. The method for preparing a coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: In terms of weight, the contents of the components in the positive electrode material are: 77-87 parts of composite lithium cobalt oxide, 6-9 parts of modified conductive agent, 4-8 parts of self-repairing binder, and 21-26 parts of deionized water.

4. The method for preparing a coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The preparation of the composite lithium cobalt oxide comprises the following steps: (1) Cobalt trioxide powder, lithium carbonate powder and magnesium oxide are mixed, ground, and kept at 1000° C. for 10 hours in an air atmosphere to obtain magnesium-doped lithium cobalt oxide; (2) Mix pyrrole, magnesium-doped lithium cobalt oxide, and anhydrous ethanol, add sodium persulfate, stir in an ice-water bath for 5-6 hours, filter, wash, and dry to obtain pyrrole-coated magnesium-doped lithium cobalt oxide; (3) 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, pyromellitic anhydride, N-methylpyrrolidone and 1,3,5-trimethylbenzene are mixed, isoquinoline is added, ultrasonic mixing is performed for 10-20 min, the mixture is transferred to a reaction tube, freeze-degassing is repeated for 3-5 times, the mixture is kept at 150°C for 5 d, the mixture is cooled, centrifuged, washed with N,N-dimethylformamide and methanol for 3-5 times, tetrahydrofuran and pyrrole-coated magnesium-doped lithium cobalt oxide are added, the mixture is ultrasonically stirred for 1-2 h, centrifuged, washed and dried to obtain composite lithium cobalt oxide.

5. The method for preparing a coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The preparation of the self-repairing adhesive comprises the following steps: In a nitrogen atmosphere, acrylamide, acrylic acid, a double-bond-terminated disulfide-containing compound and deionized water are mixed, ammonium persulfate is added, the mixture is kept warm in an oil bath at 48-52° C. for 7-8 hours, washed with ethanol for 3-5 times, and freeze-dried to obtain a self-healing adhesive.

6. The method for preparing a coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The preparation of the modified conductive agent comprises the following steps: 1) The conductive agent, isopropanol and deionized water are mixed, ultrasonically treated for 30-40 minutes, (3-mercaptopropyl)trimethoxysilane is added, the pH value is adjusted to 2.9-3.1, and the mixture is kept in a water bath at 58-62°C for 5-6 hours, filtered, washed and dried to obtain a mercapto conductive agent; 2) Mix the thiol conductive agent and n-hexane, keep warm in a 60°C water bath for 3-4 hours, add a mixed solution of a double-bond-terminated disulfide-containing compound and n-hexane, stir for 5-6 hours, add benzoin dimethyl ether, treat with ultraviolet light, wash and dry to obtain a modified conductive agent.

7. The method for preparing a coated lithium cobalt oxide positive electrode material according to claim 6, characterized in that: The conductive agent is obtained by compounding carbon black and white carbon black in a mass ratio of 2:

1.

8. The method for preparing a coated lithium cobalt oxide positive electrode material according to claim 5 or 6, characterized in that: The preparation of the double bond-terminated disulfide bond-containing compound comprises the following steps: Under a nitrogen atmosphere, 4,4-diaminodiphenyl disulfide and acetone are mixed, 2-isocyanate ethyl methacrylate is added, and the mixture is stirred at 18-25° C. for 20-21 hours, washed, and dried to obtain a double-bond-terminated disulfide-containing compound.

9. A coated lithium cobalt oxide positive electrode material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.

10. A positive electrode sheet coated with lithium cobalt oxide, characterized in that: According to the positive electrode material described in claim 9, the preparation method comprises the following steps: coating the lithium cobalt oxide coated positive electrode material on both sides of the metal foil, and drying to obtain a positive electrode sheet coated with lithium cobalt oxide.

Citation Information

Patent Citations

  • Conductive polymeric material coated lithium cobaltate positive electrode material and preparation method thereof

    CN107644986A

  • Chemically modified white graphene based on mercapto-ene click addition and preparation method thereof

    CN109850885A

  • Polysiloxane based on aromatic disulfide bond and application thereof

    CN111518279A

  • Preparation method and application of lithium battery binder with self-repairing performance

    CN111909374A

  • Long-circulation lithium battery positive electrode material and preparation method thereof

    CN117577828A

Cited By

  • Dynamic self-repairing electrode composite material and preparation method and application thereof

    CN121282172A